Leiner’s Disease (Erythroderma Desquamativum) in a Baby Boy - Ayudhia Giovanny Halim; Kun Anggi Yunanto; I Gede Mahardhita (PT Kalbe Farma Tbk., 2023)
Background: Leiner’s disease (erythroderma desquamativum) is a disorder in infants; it is a complication of seborrheic dermatitis with universal and scaly erythema (erythroderma). The case is a baby boy aged 1 month 18 days with white scaly skin for 10 days and fever for 3 days prior to hospital admission. The prognosis is good with the risk of severe infections such as pneumonia, meningitis, and sepsis if not properly treated. Latar Belakang: Penyakit Leiner (erythroderma desquamativum) adalah gangguan pada bayi yang merupakan komplikasi dermatitis seboroik; biasanya ditemukan eritema universal dan skuama (eritroderma). Kasus pada seorang bayi laki-laki berumur 1 bulan 18 hari dengan kulit kemerahan serta bersisik putih kekuningan sejak 10 hari sebelum masuk RS dan demam selama 3 hari. Prognosis baik dengan risiko infeksi berat seperti pneumonia, meningitis, dan sepsis jika tidak diterapi dengan baik.